Assessing the magnetic, cytotoxic and photocatalytic influence of incorporating Yb3+ or Pr3+ ions in cobalt–nickel ferrite - Peymani-Motlagh, Seyed Mahdi; Sobhani-Nasab, Ali; Rostami, Mojtaba; Sobati, Hossein; Eghbali-Arani, Mohammad; Fasihi-Ramandi, Mahdi; Ganjali, Mohammad Reza; Rahimi-Nasrabadi, Mehdi (Journal of materials science. Materials in electronics, 2019)
Yb 3+ - and Pr 3+ -substituted cobalt–nickel ferrite nanoparticles were prepared through a sol–gel auto-combustion procedure and the effects on the cytotoxic, photocatalytic and magnetic characteristics of the resulting compounds were evaluated. As an initial step, the structure, morphology and magnetic properties of the produced particles were assessed using X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FT-IR), scanning electron microscopy (SEM), energy dispersive X-ray (EDX), UV–visible diffuse reflectance spectroscopy (DRS), photoluminescence (PL), and vibrating sample magnetometery (VSM) techniques. The crystalline size and nanoparticles size of prepared nanostructures was in the range of 100–180 and 90–220 nm based on XRD and SEM results. Using the XRD results it was found that the product had a spinel cobalt–nickel ferrite phase structure, also containing some PrFeO 3 and YbFeO 3 phases as impurities. VSM results exhibited that Co 0.5 Ni 0.5 Pr 0.1 Fe 1.9 O 4 has higher magnetic parameters than Co 0.5 Ni 0.5 Yb 0.1 Fe 1.9 O 4 , yet but the latter enjoys enhanced photocatalytic activity in degrading methyl orange (MO) under ultraviolet (UV) light irradiation.